Women's Empowerment Counseling and the Challenges of Beneficiary Graduation: From Dependency to Independence - Imam Alfi; Lutfi Faishol; Umi Halwati; Fathurohim Fathurohim (FOUNDAE (Foundation of Advanced Education), 2026)
This research is motivated by the high dependence of beneficiaries on social assistance. Beneficiary Families (KPM) face mental, psychological, and social obstacles in achieving post-graduation economic independence, so that financial-based empowerment programs are considered not effective enough. This research aims to understand the role of empowerment counseling in the process of social assistance for graduates, especially in psychosocial, behavioral, and economic aspects, to support the transition process from dependence to sustainable independence. The approach of this study uses a descriptive qualitative method with a phenomenological analytical framework to understand the subjective experiences of beneficiaries in the local context of Banyumas Regency. Data collection was carried out through active observation, in-depth interviews, and documentation to capture the meaning, perception, and process of social assistance as experienced and interpreted by the informants. The research subjects consisted of five social companions at the sub-district level and fifty families of graduation participants from ten communities in Banyumas. Data were analyzed through the process of reduction, classification, and mapping of findings by linking field results to empowerment theory and community counseling practices. The results of the research on social assistance through community empowerment counseling for beneficiary graduates (PKH) in Banyumas indicate that empowerment counseling plays a role in supporting the independence process of participants. This research explicitly highlights women's empowerment in the transition from dependence on social assistance to economic and psychosocial independence, with empowerment counseling as a key element in the process of change. The mentoring approach through socialization, access, partnerships, and independent business development is understood as an effort to increase personal autonomy through strengthening motivation, confidence, and mindset changes. The application of cognitive restructuring techniques, motivational interviewing, support groups, and community support through KUBE and community leaders strengthens the sustainability of the graduation process